Academic background and guidance on steps to engaging young children in research - Carvalho, X.; Johnson, V; Hart, R; Colwell, J; West, A (Steps to Engaging Young Children in Research, 2014)
Since the development of the Convention on the Rights of the Child (UNCRC) in 1989, children’s right to express opinions in matters affecting their lives as articulated in Article 12 (Van Beers et al. 2006) has been increasingly recognised. This has helped to highlight their opinions and voices in broader processes of consultation and participation in key areas of child rights. Many different types of organisations, including non-governmental, networks and coalitions have joined discussion relating to children’s participation (Boyden 1997), for example Save the Children (1995) called for a ‘New Agenda for Children’. There is a range of responses to articles of the Convention and how rhetoric is translated on the ground, for example as expressed in research in Vietnam (Burr 2006), and in the separate regional interpretations of the Convention (for example in the development of a separate charter for Africa). In broader international development contexts, however, children’s participation has often been poorly understood (Theis 2010). In developed country contexts there is also the suggestion that ‘educational developments have shown little concern for children’s rights’ (Taylor 2000, p32, referring to the UK context).